1968
DOI: 10.1192/bjp.114.509.443
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Examination of Psychiatric Case Records of Patients who Subsequently Committed Suicide

Abstract: Psychiatrists have frequently pointed out that in a high proportion of individuals who commit suicide it is apparent that there is pre-existing psychiatric illness. It has been further shown that many of these people have received medical care and have been attending their doctor within four weeks of their death (Motto and Greene, 1958; Seager and Flood, 1965). The implication of these findings is that doctors do not always recognize psychiatric illness in their patients and are certainly not attuned to the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
0

Year Published

1971
1971
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(40 citation statements)
references
References 8 publications
(2 reference statements)
7
33
0
Order By: Relevance
“…This is well illustrated in the management of psychiatric patients in the ED. Some studies have shown that emergency personnel may actually increase the risk of suicide in depressed patients, 26,27 such iatrogenic contributions to suicide probably having their origin in countertransference. 28 Moral reasoning clearly has no logical validity, depending, as it does, on individual and prevailing societal and cultural values.…”
Section: Reasoning Strategiesmentioning
confidence: 99%
“…This is well illustrated in the management of psychiatric patients in the ED. Some studies have shown that emergency personnel may actually increase the risk of suicide in depressed patients, 26,27 such iatrogenic contributions to suicide probably having their origin in countertransference. 28 Moral reasoning clearly has no logical validity, depending, as it does, on individual and prevailing societal and cultural values.…”
Section: Reasoning Strategiesmentioning
confidence: 99%
“…Flood and Seager (1968) reported that of all the psychiatric suicides recorded, more than half occurred within three months of discharge and typically involved shorter hospital stays. A study exploring trends of suicide within 28 days of discharge in Scotland reported that suicide rates in females increased during the period 1968 to 1992, whereas suicide in males decreased .…”
Section: Suicide Post-dischargementioning
confidence: 99%
“…These are similar to recommendations made decades earlier such as services maintaining contact with patients and to inform relatives of their discharge (cf. Flood & Seager, 1968). The research examining the implementation of such strategies has tended to be limited and lacks evidence to suggest they have been successful.…”
Section: Suicide Post-dischargementioning
confidence: 99%
“…In a study of the records of psychiatric patients who subsequently committed suicide, Flood and Seager (1968) noted that many of these patients could be described as "dependent dissatisfied," and recommended that their recognition could serve as an aid in suicide prevention.…”
Section: Casementioning
confidence: 98%